Water quality of small seasonal wetlands in the Piedmont ecoregion, South Carolina, USA: Effects of land use and hydrological connectivity. (15th April 2015) - Yu, Xubiao; Hawley-Howard, Joanna; Pitt, Amber L.; Wang, Jun-Jian; Baldwin, Robert F.; Chow, Alex T.
Abstract: Small, shallow, seasonal wetlands with short hydroperiod (2–4 months) play an important role in the entrapment of organic matter and nutrients and, due to their wide distribution, in determining the water quality of watersheds. In order to explain the temporal, spatial and compositional variation of water quality of seasonal wetlands, we collected water quality data from forty seasonal wetlands in the lower Blue Ridge and upper Piedmont ecoregions of South Carolina, USA during the wet season of February to April 2011. Results indicated that the surficial hydrological connectivity and surrounding land-use were two key factors controlling variation in dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) in these seasonal wetlands. In the sites without obvious land use changes (average developed area <0.1%), the DOC (p < 0.001, t-test) and TDN (p < 0.05, t-test) of isolated wetlands were significantly higher than that of connected wetlands. However, this phenomenon can be reversed as a result of land use changes. The connected wetlands in more urbanized areas (average developed area = 12.3%) showed higher concentrations of dissolved organic matter (DOM) (DOC: 11.76 ± 6.09 mg L −1, TDN: 0.74 ± 0.22 mg L −1, mean ± standard error) compared to those in isolated wetlands (DOC: 7.20 ± 0.62 mg L −1, TDN: 0.20 ± 0.08 mg L −1 ). The optical parameters derived from UV and fluorescence also confirmed significant portions of protein-like fractions likely originating from land use changes such as wastewater treatment and livestock pastures. The average of C/N molar ratios of all the wetlands decreased from 77.82 ± 6.72 (mean ± standard error) in February to 15.14 ± 1.58 in April, indicating that the decomposition of organic matter increased with the temperature. Results of this study demonstrate that the water quality of small, seasonal wetlands has a direct and close association with the surrounding environment. Graphical abstract: Highlights: We collected and analyzed the water quality of forty small seasonal wetlands. Water connection has significant transfer effect for dissolved carbon and nitrogen compounds. Anthropogenic stress can change the composition of dissolved organic matters in these wetlands. Water quality of small, seasonal wetlands can reflect the change of land-use in small distance. There was no clear temporal variation of water quality in study period.